PENGARUH LEVERAGE DAN FREE CASH FLOW TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN (2012-2016) - Mangundap, Siska; Ilat, Ventje; Pusung, Rudy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This study aims to determine the effect of leverage and free cash flow on dividend policy on LQ45 index companies listed in Indonesia Stock Exchange 2012-2016. The population used in this study is the LQ45 index company listed on the Indonesia Stock Exchange 2012-2016. Method of sampling by purposive sampling according to predetermined criteria. The number of samples collected were 11 companies. Research data is secondary data obtained from Indonesia stock exchange (IDX) year 2012-2016. The collected data is analyzed by using data analysis which is done by classical assumption test before doing hypothesis testing. Hypothesis testing in this study using multiple linear regression analysis with t test, f test, and coefficient of determination. The results of this study indicate that leverage variables have a negative and significant effect on dividend policy. This suggests that leverage can affect the high dividend policy. While free cash flow has a positive and insignificant effect on dividend policy. This shows that free cash flow does not affect the high dividend policy.Keywords: leverage, free cash flow, dividend